2022
DOI: 10.1007/s40120-021-00320-w
|View full text |Cite
|
Sign up to set email alerts
|

Therapy Switches in Fingolimod-Treated Patients with Multiple Sclerosis: Long-Term Experience from the German MS Registry

Abstract: Introductions: Therapy switches in patients with multiple sclerosis (MS) receiving treatment with fingolimod occur frequently in clinical practice but are not well represented in realworld data. The aim of this study was to identify and characterize treatment switches and reveal sociodemographic/clinical changes over time in fingolimod-treated people with MS (PwMS). Methods: Data on 2536 fingolimod-treated PwMS extracted from the German MS Registry during different time periods were analyzed (2010)(2011)(2012)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In addition to demonstrating favorable real-world effectiveness that appear to be consistent with clinical trial data, this SLR highlights other important aspects of realworld ocrelizumab use in RRMS and PPMS patients; three studies report stable or improving HRQoL following up to 1 year of ocrelizumab treatment, 9,20,44 five studies reported on the clinical effectiveness of switching to ocrelizumab from natalizumab, 8,25,36,39,58 and three further studies described the effective and safe transition to ocrelizumab from other DMTs, 16,18,27 highlighting ocrelizumab as a suitable option for previously treated patients that can mitigate the risk of disease reactivation.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…In addition to demonstrating favorable real-world effectiveness that appear to be consistent with clinical trial data, this SLR highlights other important aspects of realworld ocrelizumab use in RRMS and PPMS patients; three studies report stable or improving HRQoL following up to 1 year of ocrelizumab treatment, 9,20,44 five studies reported on the clinical effectiveness of switching to ocrelizumab from natalizumab, 8,25,36,39,58 and three further studies described the effective and safe transition to ocrelizumab from other DMTs, 16,18,27 highlighting ocrelizumab as a suitable option for previously treated patients that can mitigate the risk of disease reactivation.…”
Section: Discussionsupporting
confidence: 55%
“…In the studies by Frahm et al 18 and Bigaut et al, 8 a low ARR at baseline relative to the trial and other real‐world studies was observed, which may be driven partly by the absence of treatment‐naïve patients in these studies. Notably, in the studies by Frahm et al and Bigaut et al, which capture patient groups that differ to those in the pivotal trials, ARR values following ocrelizumab were numerically lower than at baseline and of a similar magnitude to those in the other real‐world studies and the trials.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations